2021
DOI: 10.1177/0706743721990310
|View full text |Cite
|
Sign up to set email alerts
|

The Second National Canadian Homeless Youth Survey: Mental Health and Addiction Findings: La Deuxième Enquête Nationale Auprès des Jeunes Sans Abri : Résultats en Matière De Santé Mentale et de Toxicomanie

Abstract: Objective: Youth experiencing homelessness represent a major social problem in Canada and, as demonstrated in the first national survey of this population conducted in 2015, are experiencing significant mental health challenges. The present study examines the findings of a second national survey completed in 2019. These findings afford the opportunity to examine the reliability of the findings of the first study with another large, representative sample and to attempt to articulate the unique characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Abramovich, 2012;Choi et al, 2015;Durso & Gates, 2012). LGBTQ2S youth comprise nearly 20% to 40% of the overall youth homelessness population (Durso & Gates, 2012;Kidd et al, 2021). Future research should investigate the link between mental health recovery among youth who self-identify as LGBTQ2S in the context of homelessness.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abramovich, 2012;Choi et al, 2015;Durso & Gates, 2012). LGBTQ2S youth comprise nearly 20% to 40% of the overall youth homelessness population (Durso & Gates, 2012;Kidd et al, 2021). Future research should investigate the link between mental health recovery among youth who self-identify as LGBTQ2S in the context of homelessness.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…High levels of mental illness, problematic substance use, and suicidality are among the most prominent risk factors for youth who are homeless (Cronley & Evans, 2017;Narendorf et al, 2017;Perlman et al, 2014). In a recent pan-Canadian study of 1,363 youth experiencing homelessness, 74% reported experiencing mental health symptoms and high levels of distress (Kidd et al, 2021). Further, approximately one-third had at least one suicide attempt and have been hospitalized for a drug overdose.…”
mentioning
confidence: 99%
“…Although YEH suffer from a variety of poor health outcomes, challenges with mental health and addictions are most prevalent [ 5 , 6 ]. According to the most recent national youth homelessness survey (2019; N = 1375), 74% of youth respondents report high levels of distress, 35% report attempting suicide at least once and 33% report a drug overdose requiring hospitalization [ 7 ]. Additionally, YEH often suffer from physical and mental health comorbidities, and require support with health system access, navigation and coordination of health services [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Poor mental health is often associated with childhood trauma, discrimination, and the experience of homelessness itself (Kidd et al, 2018). Findings from the second and most recent national youth homelessness survey (2019) (N = 1375) indicate that 74% of youth respondents report being highly distressed, 35% report attempting suicide at least once, and 33% report a drug overdose requiring hospitalization (Kidd et al, 2021). Of those youth suffering from mental illness, 60% present with multiple diagnoses (Slesnick & Prestopnik, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicate a dose-response relationship between exposure to homelessness and mental health decline (Hadland et al, 2011;Kidd et al, 2017). Findings from the 2015 and 2019 national surveys also indicate that about 25-30% of youth seeking shelter reside at an emergency youth shelter (EYS) in Canada (Gaetz et al, 2016;Kidd et al, 2017Kidd et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%